XIV Modern Literature. Issue 1 (19th July 2021) - Ross, Shawna; Bratton, Francesca; Keese, Andrew; Binnie, Georgina; Phillips, Joshua; West, Mark; Cooper, Samuel; Stringfellow, Sophie; Rodríguez Martín, Gustavo A; Saunders, Graham; Masud, Noreen; Creasy, Matthew; et al.
Abstract: This chapter has eight sections 1. General; 2. Fiction Pre-1945; 3. Fiction Post-1945; 4. Drama Pre-1950; 5. Drama Post-1950; 6. British Poetry Pre-1950; 7. British Poetry Post-1950; 8. Modern Irish Poetry. Section 1 is by Shawna Ross; section 2(a) is by Francesca Bratton; Section 2(b) will resume in 2022; section 2(c) is by Georgina Binnie; section 2(d) is by Andrew Keese; section 2(e) is by Joshua Phillips; section 3(a) is by Mark West; section 3(b) is by Samuel Cooper; section 4(a) is by Sophie Stringfellow; section 4(b) is by Gustavo A. Rodríguez Martín; section 5 is by Graham Saunders; section 6(a) is by Noreen Masud; section 6(b) is by Matthew Creasy; section 7 is by Alex Alonso; section 8 is by Jack Quin.